مساهمة في دراسة وتقييم واقع الفحوم الهيدروجينية الاليفاتية الـ (AHCs)في الرسوبيات الشاطئية لمدينة جبلة (Latakia University Journal -Basic Sciences Series, 2018)
جمعت عينات رسوبية شاطئية من سبعة مواقع ممتدة على طول شاطئ مدينة جبلة خلال الفترة من 30/10/2000 وحتى 15/12/2001 . استخلصت هذه العينات ومن ثم تم تحليلها باستخدام تقانة الكروموتوغرافيا الغازية GC-FID وجرى استخلاصها ودراستها كيفياً وكمياً من اجل تعيين الفحوم الهيدروجينية الاليفاتية  . سجلـت تراكيز الـ (AHCs) في الرسوبيات المدروسة في المجال75.99-591.99 ng/g (dry wt. ). كانت أعلى التراكيز في المحـطة المقابلة لمصب الصرف الصحي لمنطقة الفيض والمنطقة الصناعية و المحطة الواقعة داخل مرفأ الصيد  وأخفضها في المحطة الواقعة على يمين مصب نهر الشرا شير. Samples of coastal sediments have been collected from seven sites of Jableh city during the period (30/10/2000-15/12/2001). The samples have been extracted to determine the qualitative and quantitive content of Aliphatic Hydrocarbons (AHCs), using the GC-FID technique. The concentration of (AHCs) ranges between 75.99 and 591.99 ng/g (dry wt.). The highest concentration has been reported inside the fishing port and in the station facing the discharging point of Alfied region and the industrial area sewage line; the lowest concentration has been  reported in the station located to the right of the discharging point of Al-shrasheer river .